Pengembangan Bahan Ajar Modul dengan Pendekatan Discovery Learning pada Materi Himpunan - Nanik Saputri; Isnaini Nur Azizah; Hernisawati Hernisawati (Jambura Journal of Mathematics Education, 2020)
This research generally aims to produce Module teaching material products with the Discovery Learning approach to the set material, and the specific purpose is to find out how the development and attractiveness of the Module teaching materials with that approach. This study uses the Thiagarajan 4D model development method, which consists of 4 stages, namely definition, design, development, and dissemination. The results of the research on the development of the Modules teaching material with the Discovery Learning approach. : (1) The main results of this research and development are Module teaching materials with the Discovery Learning approach. (2) Research data shows that material experts obtained an average value of 76% with the criteria of "feasible", design experts obtained an average value of 78% with the criteria of "feasible", and linguists obtained an average value of 79% with the criteria "feasible". (3) For the user's response to the teaching materials of the module with the discovery learning approach of the response of students obtained an average value of 74% with the criteria that is "interesting" and the response from educators gained a percentage of 74% with the interpretation criteria achieved namely "interesting". The significance of this research, among others, is that researchers can develop teaching material in the form of learning modules that can increase the activeness and effectiveness of students in carrying out teaching and learning in the classroom.